Urgensi Kompetensi Leadership Guru Pendidikan Agama Islam dalam Menanamkan Kedisiplinan Peserta Didik - Satariyah Satariyah; Nandar Nandar (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2022)
The Urgency of Leadership Competence of Islamic Education Teacher in Improving Student’s Discipline. The teacher’s role is not merely as a teacher but as well as an educator. The presence of the teacher is very influential in the students’ character building. One of the characteristics that need to be applied is discipline. Since discipline is one of the requirements in developing students’ character to become the next generation that will be able to compete globally. This study aimed to determine how urgent the leadership competence skill of Islamic Education teachers is in improving students’ discipline. The research method used in this study is qualitative. Whereas the type of research used library research. The results of this study were leadership competencies that the Islamic Education teacher has to possess in improving the students’ discipline. Including the ability to organize the school’s potential, and abilities as an innovator, facilitator, mentor, and counselor. In addition to the ability to maintain, control, and direct religious teachings culture in the school community. ABSTRAKGuru berperan selain sebagai seorang pengajar juga sebagai seorang pendidik. Keberadaan guru sangat berpengaruh dalam pembentukan karakter peserta didik. Salah satu karakter yang perlu ditanamkan adalah kedisiplinan. Karena kedisiplinan menjadi syarat dalam mengembangkan peserta didik menjadi generasi penerus bangsa yang mampu bersaing dalam dunia global. Penelitian ini bertujuan untuk mengetahui seberapa urgen kompetensi leadership guru Pendidikan Agama Islam dalam menanamkan kedisiplinan peserta didik. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif. Sedangkan jenis penelitian yang digunakan adalah penelitian kajian pustaka (Library Research). Hasil penelitian ini adalah kompetensi leadership yang harus dimiliki guru pendidikan agama Islam dalam menanamkan kedisiplinan peserta didik mencakup kemampuan dalam mengorganisasikan potensi sekolah, kemampuan sebagai inovator, fasilitator, pembimbing dan konselor, serta kemampuan dalam menjaga, mengendalikan, dan mengarahkan pembudayaan pengamalan ajaran agama pada komunitas sekolah. Kata kunci: Kompetensi, leadership, kedisiplinan